Changes of quality of life and cognitive function in individuals with Internet gaming disorder: A 6-month follow-up. Issue 50 (December 2016) - Lim, Jae-A; Lee, Jun-Young; Jung, Hee Yeon; Sohn, Bo Kyung; Choi, Sam-Wook; Kim, Yeon Jin; Kim, Dai-Jin; Choi, Jung-Seok
Abstract : Abstract: Internet gaming disorder (IGD) contributes to poor quality of life (QOL) and cognitive dysfunction and is increasingly recognized as a social problem in various countries. However, no evidence exists to determine whether QOL and cognitive dysfunction stabilize after appropriate management. The present study addressed improvement in QOL and cognitive functioning associated with changes in addiction symptoms following outpatient management for IGD. A total of 84 young males (IGD group: N = 44, mean age: 19.159 ± 5.216 years; healthy control group: N = 40, mean age: 21.375 ± 6.307 years) participated in this study. We administered self-report questionnaires at baseline to assess clinical and psychological characteristics, and conducted traditional and computerized neuropsychological tests. Nineteen patients with IGD completed follow-up tests in the same manner after 6 months of outpatient treatment, which included pharmacotherapy with selective serotonin reuptake inhibitors. A baseline comparison of patients with IGD against the healthy control group showed that the IGD patients had more symptoms of depression and anxiety, higher degrees of impulsiveness and anger/aggression, higher levels of distress, poorer QOL, and impaired response inhibition. After 6 months of treatment, patients with IGD showed significant improvements in the severity of IGD, as well as in QOL, response inhibition, and executive functioning. Additionally, a stepwise multiple regression analysis revealed a favorable prognosis for IGD patients with low working memory functioning and high executive functioning at baseline. These results provide evidence regarding longitudinal changes in QOL and cognitive function following psychiatric intervention for IGD. Furthermore, it appears that response inhibition may be an objective state marker underlying the pathophysiology of IGD.